Meeting. 1937, March 10, Kingsway Hall (speeches) - Longuet, Jean ; Adler, Friedrich, 1879-1960 ; Tomás, Pascual, 1893-1972 ; Schevenels, Walter, b. 1894 ; Attlee, Clement, 1883-1967 ; International Federation of Trade Unions ; Labour and Socialist International; Citrine, Walter, 1887-1983
1937-03-10 021-0034-024 292/946/21/34(xxiv)